State Laws and Nonprofit Hospital Community Benefit Spending. Issue 4 (July 2019) - Johnson, Emily K.; Hardy, Rose; Santos, Tatiane; Leider, Jonathon P.; Lindrooth, Richard C.; Tung, Gregory J.
Abstract : Objective: To determine the association of state laws on nonprofit hospital community benefit spending. Design: We used multivariate models to estimate the association between different types of state-level community benefit laws and nonprofit hospital community benefit spending from tax filings. Setting: All 50 US states. Participants: A total of 2421 nonprofit short-term acute care hospital organizations that filled an internal revenue service Form 990 and Schedule H for calendar during years 2009-2015. Results: Between 2009 and 2015, short-term acute care hospitals spent an average of 46 billion per year in total, or 20 million per hospital on community benefit activities. Exposure to a state-level community benefit law of any type was associated with an 8.42 (95% confidence interval: 1.20-15.64) per 1000 of total operating expense greater community benefit spending. Spending amounts and patterns varied on the basis of the type of community benefit law and hospital urbanicity. Conclusions: State laws are associated with nonprofit hospital community benefit spending. Policy makers can use community benefit laws to increase nonprofit hospital engagement with public health. Abstract : Supplemental Digital Content is Available in the Text.